Design of ship structural assemblies using software for topological and parametricoptimization - Gennady B. Kryzhevich (Труды Крыловского государственного научного центра, 2020)
Object and purpose of research. The paper studies hull assemblies of high speed vessels. The work purpose consists in check of effectiveness of existing recommendations on assembles design and in searching for their optimal design using numerical methods of topological and parametric optimization. Materials and methods. A comprehensive approach with using numerical methods of structural topological and parametric optimization is applied. Main results. Based on the comprehensive use of topological and parametric optimization methods and up-to-date software products, new design of assemblies of aluminum panel butt joints operating in various service conditions as a part of high speed ships was developed instead of the one recommended by the Rules of Russian Maritime Register of Shipping. Conclusion. Use of the optimal design algorithm earlier developed by the authors permitted to develop new design of assemblies of aluminum panel butt joints. These assemblies have higher low cycle and high cycle fatigue strength indicators in comparison with the ones used presently in construction of high speed ships.